"New, " "Old, " and "Nested" Institutions and Gender Justice Outcomes: A View from the International Criminal Court. Issue 4 (9th December 2014) - Chappell, Louise
Abstract : What difference do new actors and new institutions make to gender justice outcomes? This article explores this question through an examination of the objectives and influence of "new" international actors on the design and implementation of the "new" victims' rights and gender justice provisions contained in the 1998 Rome Statute of the International Criminal Court's (ICC). Highlighting the role of gender and formal and informal institutions, this article argues that during its first decade in operation, the ICC has produced mixed outcomes in terms of the treatment of victims, especially of conflict-related sexual violence. While there is some sign that the new actors and rules have helped produce some positive outcomes, there are also signs that "old" informal gender rules and the historical context in which the ICC is "nested" has contributed to undermining and distorting news rules aimed at addressing gender injustices. The article suggests that "newness" matters, but so, too, does "oldness" and "nestedness, " and understanding the interaction and relationship between these factors is key to understanding gender justice outcomes.